2015
DOI: 10.1002/joc.4468
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of vertical gradients of major meteorological observations around the Tibetan Plateau

Abstract: ABSTRACT:The near-surface air temperature lapse rate (TLR), wind speed gradient (WSG), and precipitation gradient (PG) provide crucial parameters used in models of mountain climate and hydrology. The complex mountain terrain and vast area of the Tibetan Plateau (TP) make such factors particularly important. With daily data from 161 meteorological stations over the past 43 years , we analyse the spatio-temporal variations of TLRs, WSGs, and PGs over and around TP, derived using linear regression methods and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
51
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 59 publications
6
51
3
Order By: Relevance
“…Obvious regional warming has been observed over and around the TP and the warming rates in T min are found to be higher than those of T max and T mean (Guo et al , ). Figure (b) shows scatter plots of T min trends with elevation for 1970–2012 whereas those of T max and T mean are presented in Figure S1, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obvious regional warming has been observed over and around the TP and the warming rates in T min are found to be higher than those of T max and T mean (Guo et al , ). Figure (b) shows scatter plots of T min trends with elevation for 1970–2012 whereas those of T max and T mean are presented in Figure S1, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al () analysed the long‐term (1960–2009) variations of W s in mainland China, and they found that changes of near‐surface and upper‐air W s over China correspond well to the changes in pressure gradient force and the atmospheric circulations, which provided direct evidence to support the work of Duan and Wu (). Guo et al () explored the inter‐annual (1970–2012) variations of NLRs (it has both a horizontal and vertical temperature gradient) derived from 161 meteorological stations over and around the TP and they concluded that faster warming at the higher elevations (EDW) of high‐mountain regions reduced the NLRs temporally, which directly contributed to the decreases of W s during 1970–2012 to a certain degree ( W s is a function of horizontal temperature gradient). Thus, regional weakening of W s is expected given the background of EDW over the TP and surrounding regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TP has been experiencing an overall rapid wetting and warming in recent years (Liu and Chen, ; Niu et al ., ; Yang et al ., , ; Chen et al ., ) and an interesting EDW phenomenon (Qin et al ., ; Pepin et al ., ). These phenomena are assumed to influence the hydrologic cycle and its elements, especially against the elevation due to a larger span of elevation over and around the TP (Guo et al ., , ). The topography over and around the TP was described in Figure (a) using the digital elevation model from the shuttle radar topography mission (http://srtm.usgs.gov), which generally decreases from northwest to southeast.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in surface variables are usually affected by changes in atmospheric fields such as wind speed, air temperature, geopotential height, relative, and specific humidity (Guo et al, 2016b;Li et al, 2018). There do exist positive and negative feedbacks between these atmospheric and surface meteorological fields, both in time and space.…”
mentioning
confidence: 99%